2014
DOI: 10.14689/ejer.2014.57.2
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Essay Assessment: Intra-rater and Inter-rater Reliability

Abstract: Problem Statement: There have been many attempts to research the effective assessment of writing ability, and many proposals for how this might be done. In this sense, rater reliability plays a crucial role for making vital decisions about testees in different turning points of both educational and professional life. Intra-rater and inter-rater reliability of essay assessments made by using different assessing tools should also be discussed with the assessment processes. Purpose of Study:The purpose of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 32 publications
1
17
0
4
Order By: Relevance
“…Each section was examined for dye penetration. The micro-leakage score was given by a single examiner who was blinded to the treatment and who was trained according to intra-rater agreement (31) to the following scoring system (32) : 0= no evidence of dye penetration; 1= dye penetration of less than 1/3 from the margin of restoration; 2= dye penetration of more than 1/3 and less than 2/3 from the margin of restoration; 3= dye penetration of more than 2/3 from the margin of restoration (Figure 1).…”
Section: Groupingmentioning
confidence: 99%
“…Each section was examined for dye penetration. The micro-leakage score was given by a single examiner who was blinded to the treatment and who was trained according to intra-rater agreement (31) to the following scoring system (32) : 0= no evidence of dye penetration; 1= dye penetration of less than 1/3 from the margin of restoration; 2= dye penetration of more than 1/3 and less than 2/3 from the margin of restoration; 3= dye penetration of more than 2/3 from the margin of restoration (Figure 1).…”
Section: Groupingmentioning
confidence: 99%
“…In fact, in a significant proportion of cases, scripts marked with a SGW received lower marks than the identical script marked in the standard fashion. While this may be due to the unreliability of essay marking (Kayapınar, 2014), it is also possible that the slightly different marking system for students with a SGW may have a negative impact or that examiners may be biased against some students (for example those who write well with few spelling errors and yet are claiming a waiver for spelling and grammar). Whatever the reason, findings like these are important because they contradict the common assumption that the SGW will benefit all those who receive it.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, why do the authors not report any intra-rater [3] or interrater reliability scores [4]? Previous research has shown that the reliability of scoring written material (regardless of the rating method used) is often low [5]. Was there a specific reason the idea density and the grammatical complexity scores were based on only the final ten sentences of each autobiography?…”
Section: Linguistic Ability Scoring and Reliabilitymentioning
confidence: 99%